Shakespeare, Ceremony and the Public Sphere of Performance. (2nd January 2018) - Findlay, Alison
ABSTRACT: The Globe's experiments with audience involvement have introduced novel methods of rendering spectators aware of their presence within any performance. Most of this is catered for and rehearsed, but – performance by performance – there is the opportunity for spontaneous gestures and responses. This essay focuses on this self-awareness in the Globe's 2010 productions of Merry Wives of Windsor, The Taming of the Shrew and All is True ( Henry VIII ), where the ceremony of distance between on- and offstage and between spectating and participating is questioned. As a result of this, some of Habermas' assumptions as to what a cultural "Public Sphere" might be are extended to include the theatrical potential both as a result of external factors such as expected conventions before the performance and internal nuances that bring surprise and challenge such traditions.